TROCHANTERIC FEMORAL FRACTURE UNRAVELS FUNCTIONAL METASTATIC FOLLICULAR THYROID CARCINOMA: A CASE REPORT - Ismail, Ilham; See, Chee Keong; Shudim, Saiful Shahrizal; Jasmiad, Nurbadriah; Wong, Zhe Lan; Tan, Eileen (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION In postmenopausal women, the aetiology of low-trauma trochanteric femoral fractures is often attributed to osteoporosis. However, a pathologic fracture must also be considered. Follicular thyroid carcinoma (FTC) is the second most common thyroid malignancy, but it rarely coexists with hyperthyroidism. FTC can metastasize to bone, lung and mediastinum. Functioning metastatic disease in FTC is rare but have been reported in literature. CASE We report a case of metastatic FTC presenting with a pathologic trochanteric fracture and uncontrolled hyperthyroidism. A 63-year-old female sustained a closed intertrochanteric femoral fracture following a low-trauma fall. She was receiving antithyroid medication for hyperthyroidism. Initial tests showed elevated FT4 (30.7 pmol/L), suppressed TSH and negative thyroid autoantibodies. Neck ultrasonography showed multiple thyroid nodules, including a 5.6 cm x 6.5 cm TIRADS 5 nodule. Following FNAC showing follicular neoplasm, she underwent total thyroidectomy with level 6 paratracheal lymph node dissection due to tumour infiltration of the right internal jugular vein (IJV) and parathyroid gland. Histopathology revealed a high-risk invasive FTC (pT4apN1a). Despite thyroidectomy, she remained hyperthyroid and required increased antithyroid therapy. Postoperative neck CT and carotid angiography revealed residual thyroid tissue and long segment IJV and superior vena cava thrombosis. No residual tissue was detected on re-operation. Concomitant high thyroglobulin (>5000 ng/mL) prompted F-fluorodeoxyglucose PET/CT which revealed recurrent disease at the thyroid bed, and metastases to cervical nodes, mediastinum, lungs, left femur and trochanter. CONCLUSION This illustrates a complex case of FTC coexisting with hyperthyroidism, and metastases likely to be functionally active thyroid tissue. Subsequent management would require combined surgical intervention for trochanteric fracture with local radiation therapy and radioiodine ablative therapy.